A Metal‐Free Synthesis of N‐Aryl Carbamates under Ambient Conditions. Issue 40 (12th August 2015) - Guo, Wusheng; Gónzalez‐Fabra, Joan; Bandeira, Nuno A. G.; Bo, Carles; Kleij, Arjan W.
Abstract: The first chemo‐ and site‐selective process for the formation of N‐aryl‐carbamates from cyclic organic carbonates and aromatic amines is reported. The reactions proceed smoothly under extremely mild reaction conditions using TBD (triazabicyclodecene) as an effective and cheap organocatalyst, thus providing a sustainable and new methodology for the formation of a wide variety of useful N‐aryl carbamate synthons in good to excellent yields. Computational investigations have been performed and show the underlying reason for the observed unique reactivity as related to an effective proton‐relay mechanism mediated by the bicyclic guanidine base. Abstract : By relay : The previously unknown site‐selective attack of arylamines on cyclic carbonates to deliver N‐aryl carbamates as the principal product is reported. The organocatalyst TBD guides an effective proton‐relay process, thus mediating a chemoselective formation of the carbamate target under extremely mild reaction conditions. The new methodology represents a sustainable, cheap, and attractive process towards these important N‐aryl carbamate synthons.